Short communications: Effect of red spinach (Amaranthus tricolor L. var Blitumbrum) extract in the diet on color brightnes of guppy fish (Poecilia reticulata) - Eri Yusni; Nurul F.D. Hasibuan (Aceh Journal of Animal Science, 2023)
Fish color brightness is influenced by food intake, but no prior reviews have explored the use of red spinach extract in fish feed to enhance color brightness and promote growth in guppy (Poecilia reticulata). Therefore, this study aims to determine the suitable concentration of red spinach extract Amaranthus tricolor color brightness, growth, and survival of guppy. The experiment followed a completely randomized design with three concentrations of red spinach extract (3%, 4%, and 5%) replicated three times at the UPTD Fish Breeding Center in North Binjai Regency, North Sumatra Province. Furthermore, red spinach extract was mixed with the commercial diet containing 41% crude protein and administered to fish at a rate of 3% of their body weight daily for 40 days. The results showed a significant effect of red spinach extract doses on guppy color brightness (P0.05), but no significant influence on weight gain and fish survival (P0.05). It was also discovered that the average color increase was 2,652 in feed mixed with 5% red spinach extract. Similarly, the highest fish weight gain was observed at the 5% concentration, which did not significantly differ from the other concentrations. Fish survival rates were high, with no significant differences among the treatments. Therefore, it was concluded that the optimal concentration of red spinach extract for enhancing guppy color brightness was 5%